Green Oases in the Concrete Desert: Combatting Beijing’s Heat with Urban Greenery - Wenjuan Zeng; Muan Yu (Studies in Social Science & Humanities, 2024)
In the face of rapid urbanization, Beijing confronts the escalating challenge of the Urban Heat Island (UHI) effect, characterized by significantly higher temperatures in urban areas compared to their rural surroundings. This phenomenon not only exacerbates the thermal discomfort in city environments but also poses a substantial risk to public health and well-being. Amidst this urban climate crisis, the potential of green spaces emerges as a crucial mitigative and adaptive strategy. This comprehensive study embarks on an in-depth exploration of the multifaceted role that urban greenery plays in combatting the UHI effect and bolstering the well-being of Beijing’s residents. Employing a triangulated research methodology, the study harnesses high-resolution satellite imagery to delineate the thermal footprint of green spaces within the urban matrix of Beijing. Through detailed temperature analysis, it meticulously quantifies the extent to which parks, gardens, and tree-lined avenues contribute to cooling urban environments. Complementing this quantitative analysis, the study engages with the urban populace through extensive surveys, capturing perceptions and lived experiences of the thermal environment and the subjective well-being associated with access to green spaces. The findings reveal a significant cooling effect attributed to urban greenery, with marked temperature reductions in areas with dense vegetation cover. Beyond the thermal benefits, the research uncovers a positive correlation between access to green spaces and improvements in residents’ physical and psychological health, highlighting the critical role of green spaces in promoting urban livability and sustainability. This study advances the discourse on urban planning and public health by providing empirical evidence of the benefits of integrating green spaces into the urban fabric of Beijing. It underscores the urgency of adopting green infrastructure as a standard in urban development projects, not only as a countermeasure to the UHI effect but also as a foundational element for enhancing the quality of life in densely populated urban centers. The research concludes with strategic recommendations for urban policymakers, advocating for the expansion and optimization of green spaces as indispensable assets for achieving a resilient and health-promoting urban environment in Beijing.